2010
DOI: 10.1111/j.1439-0426.2010.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of non-lethal stable isotope analysis to assess feeding patterns of juvenile pallid sturgeon Scaphirhynchus albus: a comparison of tissue types and sample preservation methods

Abstract: Summary Traditional techniques for stable isotope analysis (SIA) generally require sacrificing animals to collect tissue samples; this can be problematic when studying diets of endangered species such as the pallid sturgeon Scaphirhynchus albus. Our objectives were to (i) determine if pectoral fin tissue (non‐lethal) could be a substitute for muscle tissue (lethal) in SIA of juvenile pallid sturgeon, and (ii) evaluate the influence of preservation techniques on stable isotope values. In the laboratory, individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Andvik et al. () reported that diet differences of pallid sturgeon became detectable in both fin clips and muscle tissue after approximately 6 months. The length of time required for diet changes to become detectable by SIA must be considered when measuring temporal variation in diet as well as determining timing of diet ontogeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andvik et al. () reported that diet differences of pallid sturgeon became detectable in both fin clips and muscle tissue after approximately 6 months. The length of time required for diet changes to become detectable by SIA must be considered when measuring temporal variation in diet as well as determining timing of diet ontogeny.…”
Section: Discussionmentioning
confidence: 99%
“…MacNeil et al (2006) found that the length of time to detect diet changes using d 15 N varied among tissues, with more metabolically active tissue (i.e., liver) reflecting diet changes more rapidly than less metabolically active tissue (i.e., cartilage) in freshwater stingrays (Potamotrygon motoro). Andvik et al (2010) reported that diet differences of pallid sturgeon became detectable in both fin clips and muscle tissue after approximately 6 months. The length of time required for diet changes to become detectable by SIA must be considered when measuring temporal variation in diet as well as determining timing of diet ontogeny.…”
Section: Discussionmentioning
confidence: 99%
“…Different storage methods may alter the isotopic signatures of the scale tissue, necessitating the need to identify the impacts of preservation techniques (Kelly et al. 2006a; Andvik et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Scale envelopes were not used in this study, but this is a common practice when removing and cataloguing scales for ageing purposes. Different storage methods may alter the isotopic signatures of the scale tissue, necessitating the need to identify the impacts of preservation techniques (Kelly et al 2006a;Andvik et al 2010). Overall, because of the disparities in isotopic signatures between the different tissue types, it is recommended to use muscle tissue whenever available, unless a small subset of organisms can be sacrificed for tissue comparisons.…”
Section: Non-lethal Sampling Of Walleye For Stable Isotopes 287mentioning
confidence: 99%
“…Previous studies have relied upon stable‐isotope values in muscle and fin tissue to reconstruct fish trophic position (Overman & Parrish, 2001; Dalerum & Anjerbjörn, 2005; Sanderson et al , 2009; Andvik et al , 2010). Research demonstrates, however, that scale tissue provides a reliable isotopic indication of trophic position (Wainright et al , 1993; Perga & Gerdeaux, 2003; Pruell et al , 2003; Jardine et al , 2005; Grey et al , 2009).…”
Section: Introductionmentioning
confidence: 99%